Kombinasi Sari Belimbing Wuluh (Averrhoa bilimbi L.) dan Sari Wortel (Daucus carota L.) terhadap Mutu Permen Jelly - Resty Rahayu; Noviar Harun; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was obtained the best ratio of bilimbi extract and carrot extract in making jelly candy. The research was used completely randomized design (CRD) with five treatments and three replications which followed by Duncan’s New Multiple Range Test (DNMRT) at 5% level. The treatment of this research were BW1 (bilimbi extract 90:10 carrot extract), BW2 (w bilimbi extract 80:20 carrot extract), BW3 (bilimbi extract 70:30 carrot extract), BW4 (bilimbi extract 60:40 carrot extract) and BW5 (bilimbi extract 50:50 carrot extract). The result of analyz was showed that the ratio of extract bilimbi and carrot significantly affected on moisture content, ash content, pH, reduction sugar content, descriptive of sensory test on colour, flavour, taste, texture, hedonic of sensory test on colour, taste, texture and overall test before coated sugar and tapioca flour (1:1), but did not significantly affected hedonic sensory of flavor of jelly candy and overall test after coated sugar and tapioca (1:1). The best formulation jelly candy were BW4 with water content 9.31%, ash content 0.78%, pH 4.28, reduction sugar content 22.02% with description score 3.94 (colour), 3.54 (flavour), 3.72 (taste), 3.76 (texture ) and 4.10 (overall). Keywords: jelly candy, bilimbi extract and carrot extract